(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article highlights various threats and their manifestations that have a negative impact on the spirituality of youth in the modern era of globalization. The place of these variants of threats in a person’s life, their dictionary meaning, negative consequences, and ways to eliminate them are also shown.